LA CAPACITACIÓN DE ]ÓVENES CON DISCAPACIDAD: Una experiencia de servicio social en Montetrrey, Nuevo León - Azoh, José (2000)
The purpose of this paper is to emphasise the importance of education and training for young people with disabilities as prerequisites for a full integration and also as a basic aspect in overcoming poveny. The argument developed is based on an experience of capacitation among a group of disadvantaged young people with disabilities in Monterrey, Nuevo León and carried out by retired school teachers.